Listening to Sexual Minorities on Christian College Campuses - Yarhouse, Mark A. (Journal of psychology and theology, 2009)
This study investigated two areas of interest in the literature on sexual minorities: milestone events in sexual identity development and campus climate for sexual minorities in young adulthood. What is unique is that the information is obtained from Christian sexual minorities attending Christian colleges or universities. A sample of 104 undergraduate sexual minority students at three Council of Christian Colleges and Universities (CCCU) member institutions completed an anonymous online survey. The questionnaire asked sexual minorities for information on their experiences of campus climate as well as perceptions of campus resources, coping activities, and recommendations for campus, religious institutions, and other sexual minorities. Respondents also completed information on milestone events in sexual identity development. The results of the survey are a descriptive analysis of contextualized “voices” that relate a collective story for these representative institutions.